Two new species of Pasipha Ogren & Kawakatsu (Platyhelminthes: Continenticola) from areas of deciduous forest in southern Brazil - Amaral, Silvana Vargas Do; Leal-Zanchet, Ana Maria (Zootaxa, 2016)
Two new species of Geoplaninae from southern Brazil are described herein. The new species, belonging to the genus Pasipha Ogren & Kawakatsu, 1990, can be distinguished from each other and from their congeners by colour pattern and characteristics of the copulatory apparatus, especially regarding the female organs and prostatic vesicle. Both new species seem to be endemic to areas covered by deciduous forest.